Open and hidden reserves in accounting system and reporting of enterprises - Krupka, Yaroslav (Herald of Economics, 2021)
Introduction. The development strategy of the firm or company must take into account various systemic and non-systemic risks and to minimize or avoid them, create the necessary financial sources in the form of reserves, collateral, insurance reserves and more. The reserve system of the enterprise provides for the official regulatory provision of funds to cover unforeseen expenses and losses, the creation of provisions for future expenses, the formation of reserves to cover doubtful and bad debts. In addition, companies can create and use hidden reserves, which are not provided by the accounting system and reporting, but play an important role in ensuring the activities of economic entities.Purpose. The main aim of the article is to analyze the structure and importance of different types of reserves and provisions, their role in stabilizing and effective activities of enterprises and corporations, determining the place of hidden reserves, providing suggestions on how to assess them.Method. The following methods are used in the research: monographic - to study the literature of the reservation system; regulatory support - to assess its availability and needs, compliance and violations; analytical - for analytical assessment of the feasibility of creating and efficient use of reserves and provisions; logical - for the purpose of legal and economic assessment of hidden reserves of enterprises and corporations.Results. An important means of protecting enterprises and corporations from systemic and non-systemic risks, including the consequences of a coronavirus pandemic, should be a rationally constructed backup system. It provides the formation of both open regulatory reserves and the search and use of hidden reserves and collateral. The interest of enterprises to increase the amount of open reserves can be achieved by reflecting in the balance sheet and other reporting of such sources in equity. In addition to the actual reserve capital created in accordance with the established standards through deductions from net income, hidden reserves and collateral must include unidentified collateral, when the time of occurrence of the relevant costs, their size, as well as the name of the creditor, or when payments for expected costs may not be known. The allocation of such reserves to equity will improve the estimated indicators of financial stability, investment attractiveness of economic entities. Among the hidden reserves should be distinguished reserves to improve the efficiency of economic activity, which are determined by the results of a detailed analysis of performance indicators. Certain resources may be released as a result of establishing an optimal accounting policy in the enterprise. Instead, it is necessary to timely identify and avoid concealment of the results of mismanagement, inaccurate presentation of information in accounting and reporting. Perspectives. Creating a reliable reserve system, its full information representation in accounting and reporting will protect companies from systemic and non-systemic risks, and the ability to objectively assess real and hidden reserves will allow real and potential investors to properly navigate in assessing the investment attractiveness of businesses.